Impact of coronary bypass or stenting on mortality and myocardial infarction in stable coronary artery disease. (15th June 2020) - Taglieri, Nevio; Bruno, Antonio G.; Bacchi Reggiani, Maria Letizia; D'Angelo, Emanuela C.; Ghetti, Gabriele; Bruno, Matteo; Palmerini, Tullio; Rapezzi, Claudio; Galiè, Nazzareno; Saia, Francesco
Abstract: Background: To assess whether coronary bypass (CABG) or stenting reduce the risk of mortality and myocardial infarction (MI) compared with optimal medical therapy (OMT) in stable coronary artery disease (CAD). Methods: We performed a systematic review and network meta-analysis of contemporary randomized controlled trials comparing OMT, CABG and different stent types in stable CAD. All-comer trials were included if the rate of patients with acute myocardial infarction (AMI) was≤20%. Endpoints were all-cause mortality and MI. Results: Ninety-seven trials including 75, 754 patients were analyzed at a weighted mean follow up of 42.5 months. Compared to OMT, CABG was associated with a lower risk of death (OR = 0.84; 95%CI:0.71–0.97). After exclusion of trials in left main and/or multivessel disease(LM/MVD) this benefit was not statistically significant (OR = 0.89; 95%CI:0.74–1.06). CABG was associated with a lower risk of MI (OR = 0.67;95%CI: 0.49–0.91) showing, however, a certain degree of inconsistency ( p =0.10). None of the stent types included was associated with a lower risk of death. However, durable-polymer-CoCr-everolimus-eluting stent, by mixed evidence, after exclusion of either LM/MVD (OR = 0.73;95%CI: 0.54–0.98) or all-comer/post-MI trials (OR = 0.62;95%CI:0.39–0.98) was associated with a lower risk of MI than OMT. Similar findings, by indirect evidence, were confirmed for bio-absorbable-polymer-CoCr-sirolimus eluting stent (LMV/MVD trials excluded OR = 0.46; 95%CI = 0.29–0.74, all-comer/post-MI trials excluded: OR = 0.41;95%CI:0.22–0.79). Conclusions: In stable CAD, CABG reduces the risk of mortality and MI compared to OMT, especially in patients with higher extent of CAD. Our study suggests that some of second and latest-generation drug-eluting stents may reduce the risk of MI. Future research should confirm these latter findings. Highlights: In patients with stable CAD coronary bypass reduces the risk of death and MI. None of the stent type were associated with mortality reduction. DP-CoCr-EES and BP-CoCr-SES reduce the risk of MI in patient at lower extent of CAD.